The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/anie.202201577
|View full text |Cite
|
Sign up to set email alerts
|

Triggering near‐infrared luminescence of vanadyl phthalocyanine by charging

Abstract: Probing electrofluorochromism (EFC) at the molecular level remains challenging. Here we study the strongly charge state-dependent photoluminescence of vanadyl phthalocyanine. We report vibrationally resolved absorption and laser-induced fluorescence (LIF) spectra of samples comprising both the mass-selected neutral molecule (VOPc * , a stable radical) and its cation produced upon electron ionization (EI) isolated in 5 K neon matrices. Ionization of the essentially non-emissive VOPc * forms a high-spin diradica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We chose FCHT rather than FC as the former predicted slightly better agreement with our experimental spectra. Moreover, in our previous studies of rigid cationic dyes FCHT has delivered better agreement with the experimental spectra [see refs and ]. A comparison of the experimental (top panel) and predicted (bottom panel) vibronic spectra of [PY] + is presented in Figure and listed in Tables S3–S4 (Table S5 lists all of the calculated vibrational frequencies in the ground and excited state).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We chose FCHT rather than FC as the former predicted slightly better agreement with our experimental spectra. Moreover, in our previous studies of rigid cationic dyes FCHT has delivered better agreement with the experimental spectra [see refs and ]. A comparison of the experimental (top panel) and predicted (bottom panel) vibronic spectra of [PY] + is presented in Figure and listed in Tables S3–S4 (Table S5 lists all of the calculated vibrational frequencies in the ground and excited state).…”
mentioning
confidence: 67%
“…We have recently reported that a combination of two complementary experimental methods each implemented for measurements of samples at 5 K provides a powerful approach to explore both the ground and excited electronic states of a given chromophore in different charge states at high spectroscopic accuracy. These are (a) messenger-tagging PD spectroscopy together with (b) matrix isolation spectroscopy (MIS) of electrosprayed ions soft-landed into inert gas. Their joint application allows us to routinely obtain PD and DF spectra with well-resolved vibronic structure and narrow line width even for relatively large molecular ions with more than 50 atoms. , Here we have used this approach to study isolated [PY] + electrosprayed from solution and then mass-selected in the gas phase.…”
mentioning
confidence: 99%
“…Among numerous NIR fluorescent organic dyes based on cyanines, phthalocyanines (Debnath et al, 2022), BODIPYs (Boens et al, 2012), and rhodamine analogs (Liu & Scott, 2021), heptamethine cyanine dyes have secured their place in early tumor diagnosis due to some intriguing features including little side effects, deep tissue infiltration, and low fluorescence background in living organisms (Yuan et al, 2013). Impressively, indocyanine green (ICG), a traditional heptamethine cyanine dye, has been approved by the United States Food and Drug Administration (FDA) for clinical applications (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In addition to color changes, electrofluorochromic (EFC) effect, referring to the phenomenon that the emission color, wavelength, and intensity of a material alter reversibly under electrical stimulus, can modulate the emission properties, which also has tremendous application potential in electronic devices such as smart displays. [5][6][7] The fluorescence of EFC materials can be switched between ON/OFF or different colors under the drive of the specific electrochemical redox reactions. [8][9][10] However, reflective EC displays strongly relies on light sources for their operation and cannot be applied in nighttime or dark environments, which requires emission mode displays containing EFC materials to effectively supplement them.…”
Section: Introductionmentioning
confidence: 99%